If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 6) = -9(3 + 2x) Reorder the terms: 9(6 + x) = -9(3 + 2x) (6 * 9 + x * 9) = -9(3 + 2x) (54 + 9x) = -9(3 + 2x) 54 + 9x = (3 * -9 + 2x * -9) 54 + 9x = (-27 + -18x) Solving 54 + 9x = -27 + -18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18x' to each side of the equation. 54 + 9x + 18x = -27 + -18x + 18x Combine like terms: 9x + 18x = 27x 54 + 27x = -27 + -18x + 18x Combine like terms: -18x + 18x = 0 54 + 27x = -27 + 0 54 + 27x = -27 Add '-54' to each side of the equation. 54 + -54 + 27x = -27 + -54 Combine like terms: 54 + -54 = 0 0 + 27x = -27 + -54 27x = -27 + -54 Combine like terms: -27 + -54 = -81 27x = -81 Divide each side by '27'. x = -3 Simplifying x = -3
| 7m-15-10m=6 | | (3y+5)=(4y-10) | | 5x^2=2+3x | | 5w+6-w=2 | | 4x+6=2x^2 | | 5x^2+2=3x | | 0=9x^2-39x+24 | | 25+1.75x=10+3.25x | | 6=y^2+5y | | 125=.005s^2+1.1s | | 2p^2-13p-20= | | -x+6(6x+2)=-2+7(-4+11) | | 0.04(4-1)=0.03(-1+8)+0.04 | | h=40t-5t^2 | | 18x^2+23x-6=0 | | 17n=-4 | | -4(n+3)-6=-2(n-7) | | 4y^2+y-3=0 | | 7r^2+48r-7= | | -(x+11)=9 | | -3(-9+x)=24 | | 3(a+2)=2(a-7) | | 11(4x+11)=-2 | | -4(-3+x)=48 | | 4(x-5)=3x-8 | | 2(-4+a)=-24 | | 6x-7x=12 | | 8g+18=62 | | 2(3+k)=2 | | 8y+328=4y | | 3x+9=42 | | 3(-2-4)=2(5-2+1) |